Evaluation, Beneficiation and Utilization of Glass- Sands of Kerala - Sathy Chandrasekhar , D. Thomas , M. Lalithambika & S. Ravindra Reddy (Transactions of the Indian Ceramic Society, 1986)
Quartz sand deposits of Kerala are mainly confined to the Alleppey- Cbavakkacl belt on the western coast of Kerala. For evaluating this rich deposit, extensive physico-chemical characterization bas been carried out. The feasibility of utilizing this resource in the prepara- tion of vitrified flooring tiles, refractory bricks, silicon carbide, optical and opbtbalmic glasses and In foundry applications bas been diSCII!iSed